DEVELOPMENT OF SPORTS IN UZBEKISTAN: DEVELOPMENT OF SPORTS IN UZBEKISTAN - Karimov, Davron (Maktabgacha taʼlim jurnali, 2021)
the article is devoted to the development and dissemination of national sports in Uzbekistan. It covers the state policy regarding the preservation and popularization of national sports and national games, which are held regularly and universally in order to attract the population, especially the youth. For centuries, the Uzbek people have been famous for their wrestlers Palvana and legendary equestrians who are the founders of the national sports of Uzbekistan, such as kurash, belbogli kurash, turon and boykurgan. Keywords: youth, sports, sports games, national sports, folk games.